Comprehensive optimisation of China's energy prices, taxes and subsidy policies based on the dynamic computable general equilibrium model. (1st July 2015) - He, Y.X.; Liu, Y.Y.; Du, M.; Zhang, J.X.; Pang, Y.X.
Highlights: Energy policy is defined as a complication of energy price, tax and subsidy policies. The maximisation of total social benefit is the optimised objective. A more rational carbon tax ranges from 10 to 20 Yuan/ton under the current situation. The optimal coefficient pricing is more conducive to maximise total social benefit. Abstract: Under the condition of increasingly serious environmental pollution, rational energy policy plays an important role in the practical significance of energy conservation and emission reduction. This paper defines energy policies as the compilation of energy prices, taxes and subsidy policies. Moreover, it establishes the optimisation model of China's energy policy based on the dynamic computable general equilibrium model, which maximises the total social benefit, in order to explore the comprehensive influences of a carbon tax, the sales pricing mechanism and the renewable energy fund policy. The results show that when the change rates of gross domestic product and consumer price index are ±2%, ±5% and the renewable energy supply structure ratio is 7%, the more reasonable carbon tax ranges from 10 to 20 Yuan/ton, and the optimal coefficient pricing mechanism is more conducive to the objective of maximising the total social benefit. From the perspective of optimising the overall energy policies, if the upper limit of change rate in consumer price index is 2.2%, the existing renewable energy fund should be improved.